2017
DOI: 10.3390/jlpea7040028
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Stage Classification by a Combination of Actigraphic and Heart Rate Signals

Abstract: Abstract:Although heart rate variability and actigraphic data have been used for sleep-wake or sleep stage classifications, there are few studies on the combined use of them. Recent wearable sensors, however, equip both pulse wave and actigraphic sensors. This paper presents results on the performance of sleep stage classification by a combination of heart rate and actigraphic signals. We studied 40,643 epochs (length 3 min) of polysomnographic data in 289 subjects. A combined model, consisting of autonomic fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…89,90 Combining heart rate variability with accelerometry data may help improve the accuracy of sleep measurement; however, the results to date do not suggest that combining these technologies improves sleep measurement. 91,92 Interestingly, the latest generation of wearable devices are now capable of measuring cardiac activity via photoplethysmography optical sensors, wherein these sensors provide a supplement to accelerometry in the classification of sleep and wake. Preliminary investigations suggest that these devices provide comparable estimations of sleep versus wake to research-grade accelerometry devices.…”
Section: Novel Technologies For Measuring Time-use Activity Behaviourmentioning
confidence: 99%
“…89,90 Combining heart rate variability with accelerometry data may help improve the accuracy of sleep measurement; however, the results to date do not suggest that combining these technologies improves sleep measurement. 91,92 Interestingly, the latest generation of wearable devices are now capable of measuring cardiac activity via photoplethysmography optical sensors, wherein these sensors provide a supplement to accelerometry in the classification of sleep and wake. Preliminary investigations suggest that these devices provide comparable estimations of sleep versus wake to research-grade accelerometry devices.…”
Section: Novel Technologies For Measuring Time-use Activity Behaviourmentioning
confidence: 99%
“…Yucelbas, S., et al compared the results of four different classification methods to classify 3-class sleep staging for healthy people, achieving the highest accuracy of 87.11%, but only 78.08% for patients with obstructive sleep apnea [17]. While another research using ECG and acceleration signals only achieved the accuracy of 74.5% [18]. Since the RRV based features can be extracted from ECG signals [19], the sleep staging methods involved HRV and RRV features can be simply implemented by using single-lead ECG signals.…”
Section: Introductionmentioning
confidence: 99%
“…For example, during non-rapid eye movement (REM) sleep, there is an increase in high-frequency power and a decrease in low-frequency power of heart rate variability; during REM sleep and wake, the opposite is true. [12][13][14] Studies using research-grade devices have demonstrated the benefits of heart rate and heart rate variability assessment for sleep classification. [12][13][14] However, it remains less clear whether the addition of heart rate and heart rate variability measurement adds to the accuracy of sleep detection in consumer wearable devices.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Studies using research-grade devices have demonstrated the benefits of heart rate and heart rate variability assessment for sleep classification. [12][13][14] However, it remains less clear whether the addition of heart rate and heart rate variability measurement adds to the accuracy of sleep detection in consumer wearable devices. Results from several studies suggest that consumer wearable devices with heart rate technology are comparable to actigraphy for the differentiation between sleep and wake, but accurate detection of sleep stages remains poor.…”
Section: Introductionmentioning
confidence: 99%